STRATEGI KEBERLANJUTAN PASCA PANDEMI COVID-19 PADA INDUSTRI KREATIF BERBASIS PONTENSI DAERAH (Studi Kasus UMKM UD Arshaindo Gresik) - narto narto; Dwi Junianto; Gatot HM (JURNAL REKAYASA SISTEM INDUSTRI, 2022)
Micro, Small, and Medium Enterprises (MSMEs) are creative industries that are able to contribute to improving the national economy during the Covid-19 pandemic. Creative industries that manage regional potential results are expected to play an important role in reducing global impacts after the Covid-19 pandemic. UD Arshaindo, one of the MSMEs in managing fish ponds, is a leading potential in Gresik Regency. Several factors were faced during the pandemic, resulting in a decline in sales levels. Various leniency policies given by the government at the beginning of 2022, provided an opportunity for MSME actors to rise up to make various performance improvements. To overcome this, a sustainability strategy is needed to be able to be competitive after the Covid-19 pandemic. For that, we need internal and external analysis using the SWOT method through mapping strengths, weaknesses, opportunities, threats. The purpose of this study was to determine the condition of UD Arshaindo's MSMEs during the Covid-19 pandemic and to develop a sustainability strategy after the Covid-19 pandemic in the creative industry based on regional potential. The results showed that UD Arshaindo was in quadrant V. The alternative sustainability strategy made was the addition of raw material supply and production machinery to produce quality products, building cooperation partners with local governments in the field of empowering pond processing that produces fish as the main raw material for products and inter-regional retail to increase market segmentation by maximizing digital technology platforms.